Level of awareness on occupational safety and health among employees in Alpha Industries Sdn Bhd / Siti Norshazwanie Mohd Fikri - Mohd Fikri, Siti Norshazwanie (Faculty of Business and Management, 2019)
Knowledge about Occupational Safety and Health (OSH) is important in organization as it is a critical factor for ensuring employees’ safety at workplace. In addition, this issue will somehow impact the organization in order to achieve their targets and goals. Therefore, this study seeks to examine factors that can influence employee’s level of awareness on OSH. The objective of this study is to identify the factors that influence employee’s level of awareness on OSH in Alpha Industries Sdn. Bhd such as information and training provided, role of safety and health committee and employee commitment. The sampling technique that was used in this study is proportionate stratified sampling and the data collection was used is questionnaire. The researcher have distribute 110 questionnaire to 124 of the respondents, then get the return questionnaire of 97 of the respondents. The data that had been collected was then evaluated by using Statistical Package for the Social Science (SPSS) Software version 22. and data was formulate such as reliability, frequency, descriptive, Pearson’s correlation and multiple regression analysis. The results indicated from the factors which include information and training provided and employee commitment are related to employee’s level of awareness on OSH have significant relationships with dependent variable and role of safety and health committee were found to have no significant relationships with dependent variable. However, based on the result it had been found that there are other independent variable that can influence employee’s level on awareness on OSH which is not included in this study.